Gastritis cystica profunda: Endoscopic ultrasound findings and review of the literature - Machicado, Jorge (Medknow Publications & Media Pvt Ltd, 2014)
Gastritis cystica profunda (GCP) is a rare pseudotumor of the stomach characterized by benign growths of deep gastric glands through the muscularis mucosae into the submucosa. We review a case of GCP in a 61-year-old patient with GCP, with emphasis on endoscopic ultrasound findings and present review of the current literature.